Exploring how limiting the number of ball touches during small-sided games affects youth football players’ performance across different age groups - Coutinho, Diogo (2022)
This study explored how the number of allowed ball touches per player possession affected the performance of different age groups (U9, U11, U13, U15, U17 and U19) during a Gk + 4vs4+Gk small-sided games. Each day, players randomly performed the following three conditions (for a total of 6 days): i) free-play (FP); ii) maximum of 2 touches (2 T); iii) 1 touch (1 T). Players’ positional data was used to compute time-motion and positional-related variables, while video analysis was used to capture technical performance. In general, no effects were identified in relation to the players distances (team centroid, opponents’ centroid, nearest teammate, and nearest opponent). There were small to moderate decreases in the longitudinal synchronization while playing with 1 T and 2 T in the U9 and U17, but a moderate increase in the U15. There was a general decrease in the distance covered and distance covered while running (small to moderate effects) when playing with limited touches in all age groups. Limiting the touches promoted small to moderate increases in the number of successful passes in the U9, U15, and U17 and a general increase in unsuccessful actions. Overall, playing with limited touches emphasized the passing skill while it also contributed to more unsuccessful actions and lower physical demands. As so, coaches may use the 2 T in young age groups (U9-U13) as they seem less able to successfully cope with 1 T, while using 1 T in older age groups due to their higher ability to interact with environmental information.